PENGARUH KARAKTER ENTREPRENEUR TERHADAP MINAT BERWIRAUSAHA (Studi Empiris Pada Santri di Pondok Pesantren Al-Ittifaq Ciwidey Bandung) - Miko Polindi (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2019)
This research is based on seeing the success of some students of Al-Ittifaq Pesantren who become entrepreneurs. The purpose of this study is to find out how much influence the entrepreneur character of entrepreneurship interests of boarding school students al-ittifaq Ciwidey Bandung. With the rationale based on the theory proposed by William D. Bygrave, Suryana, Theo Suhardi and Slameto which suggests that in general the factors that affect one's entrepreneurial interest is the factor of personality (from within oneself). So from this theory researchers used entrepreneur character variables as an independent variable and entrepreneurship interest as a dependent variable. The research method used in this research is descriptive method verifikatif, through survey with data collection techniques using questionnaire and observation. The samples taken were 10% of the total population using the Slovin formula. The results of this study conclude that there is a positive but not significant influence between entrepreneur character variables on entrepreneur interest. Where the amount of influence that is equal to 0.39%. There is a positive influence on this variable, in line with the theory proposed by Suryana which reveals that one of the factors that influence one's entrepreneur interest is personal factor (character / character).